Features of the anatomical structure of leaves depending on the high-altitude growth of apricot in Dagestan - D. M. Anatov; Z. M. Asadulaev; Z. R. Ramazanova; R. M. Osmanov (Труды по прикладной ботанике, генетике и селекции)
Background. The adaptive changes during the distribution of Prunus armeniaca L. in Dagestan are important for understanding microevolution, structural and functional differentiation processes of populations along environmental gradients based on the organism’s reaction norm. They can be examined by studying leaf anatomical features, having ecologically differentiating significance in natural populations with contrasting growth conditions.   Materials and methods. The material for the study of leaf anatomical features was taken from 7 apricot trees in 3 growing areas of Mountainous Dagestan. Comparative analysis was carried out for 42 morphological, anatomical and index parameters of the lamina and petiole.   Results. The anocytic structure type of the stomatal apparatus was found in all apricot samples. The differences were determined by the degree of stomata submergence depending on the cuticle’s development. Trees from greater heights had more trichomes on the leaf’s upper side than on its underside. Significant differences between the extreme height reference points were recorded for the number of stomata, cells of the lower epidermis, layers of the sclerenchyma, and xylem thickness. Most of the traits of the lamina decreased, and those of the petiole increased with the altitude.   Conclusion. The traits corresponding to the lower and upper altitude limits of P. armeniaca were identified on the basis of the lamina and petiole anatomical features. More xerophytic leaf traits were recorded for the altitudes of 550 m and 1900 m, and mesophytic ones for 1700 m and 1800 m. Endoderm thickness, number of endosperm layers, petiole index, and stomatal index were identified as stable indicators according to the reaction norm within the scope of altitudes: The differences were proved for more plastic traits (number of cells of the upper and lower epidermis, number of stomata, thickness of the lamina and cuticle, and the petiole’s long axis diameter).